2013
DOI: 10.3389/fpls.2013.00021
|View full text |Cite
|
Sign up to set email alerts
|

Plant-bacterium interactions analyzed by proteomics

Abstract: The evolution of the plant immune response has resulted in a highly effective defense system that is able to resist potential attack by microbial pathogens. The primary immune response is referred to as pathogen associated molecular pattern (PAMP) triggered immunity and has evolved to recognize common features of microbial pathogens. In response to the delivery of pathogen effector proteins, plants acquired R proteins to fight against pathogen attack. R-dependent defense response is important in understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 99 publications
(163 reference statements)
0
16
0
1
Order By: Relevance
“…Here we extended earlier proteomic analyses of microbial plant community members (10,56,57) by applying the massively parallel targeted proteomic technique SWATH MS to reliably quantify the proteomic changes of two ubiquitous plant commensals upon colonization of A. thaliana leaves. Methylobacterium and Sphingomonas are two genera commonly inhabiting the phyllosphere of different host plants and previous studies suggested distinct metabolic capabilities to be important drivers for niche separation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Here we extended earlier proteomic analyses of microbial plant community members (10,56,57) by applying the massively parallel targeted proteomic technique SWATH MS to reliably quantify the proteomic changes of two ubiquitous plant commensals upon colonization of A. thaliana leaves. Methylobacterium and Sphingomonas are two genera commonly inhabiting the phyllosphere of different host plants and previous studies suggested distinct metabolic capabilities to be important drivers for niche separation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few reports are available on combinational effects of beneficial microbes and salt stress through protein study, and these show that most of the expressed proteins in plants under salinity stress are related to transcription and translation factors, photosynthesis, lignin biosynthesis, and antioxidative and defense proteins (Cheng et al, 2012;Vaishnav et al, 2015;Singh et al, 2017). However, plant growth response to microbial application may vary with the experimental conditions, microbial diversity, and plant functional groups (Afroz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the proteins in the symbiosis process function as a complex network, which combines complex chemical, physical and biological interactions between rhizobial bacteria and their host plants [8]. To better elucidate the complex microbial communities and investigate the mechanism of nitrogen-fixing symbiosis, it is necessary to construct the protein interactions between rhizobium and their host legume plants [9].…”
Section: Introductionmentioning
confidence: 99%